Termična analiza tankih plasti - Cerc Korošec, Romana (Vakuumist, 2002)
A review of different ways of thermal analysis of thin films, especially on the field of thermogravimetry and dynamic scanning calorimetry is reported. The basic principle of thermomangetometry, emanation application of thermal analysis of thin films for optimization of electrochromic effect of nickles oxide thin films, perpared by sol-gel route, will be presented in part 2.
Keywords: tanke plasti; termična analiza; termogravimetrija; kalorimetrija; diferenčna dinamična kalorimetrija